TRANSGRESSIVE SEQUENCES ON FORELAND MARGINS: A CASE STUDY OF THE NEOGENE CENTRAL GUADALQUIVIR BASIN, SOUTHERN SPAIN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The Guadalquivir foreland basin, located between the Iberian basement northward and the Betic orogen to the South, represents the western sector of the earlier foredeep basin of the Betic Cordillera. Along the northern foreland margin, the sedimentary fill of this basin includes a Tortonian Basal Transgressive Complex (BTC), composed of five internal sequences bounded by transgressive surfaces. Two main parts are distinguished within each sequence: the lower transgressive lag deposits, and the upper stillstand/prograding sediments. Three facies associations were distinguished within this stratigraphic succession along the central sector of this basin margin: unfossiliferous conglomerates and coarse-grained sands (A), fossiliferous conglomerates and coarse-grained sands (B), and yellow medium-coarse-grained fossiliferous sands (C). A fourth facies association (D: blue silty marlstones and shales) overlies the BTC. Deposits of alluvial sediments (facies association A) and shallow-marine/foreshore sediments (facies association C), were recurrently interrupted by transgressive pulses (facies associations B and C). Every pulse is recorded by an erosional, cemented sandy-conglomerate bar with bivalves (Ostreidae, Isognomon), balanids, gastropods and other marine bioclasts; or their transgressive equivalents. The lateral facies changes in each individual sequence of the BTC are related to: (1) the influence on the northern foreland margin of the tectonic activity of the southern orogenic margin; (2) the palaeorelief formed by irregularities of the substrate which controls the sediment dispersal; and (3) the evolution stages of the sedimentary systems.